Historical Epochs of Local Government Administration in Nigeria: Women and the Poor (Global Journal of Human-Social Science, 2012)
Local Government administration and development in Nigeria has, historically, undergone a number of epochs: Native Authority or Indirect Rule system; Local Administration system; Democratization of the system and the separation of traditional/ emirate council from democratic Local government system. The last of these epochs is the most spectacular in the way it deepened and still deeps democracy at local government level. To date, this last epoch has had not less than nine reforms: The 1976 Guidelines for Local Government Reform; The 1979 Constitution of the Federal Republic of Nigeria; The 1984 Dasuki Report on the Nigerian Local Government system; The 1988 Civil Service Reforms in the Local Government system; The 1989 Constitution of the Federal Republic of Nigeria; The 1992 Handbook on Local Government Administration; The 1989 Constitution of the Federal Republic of Nigeria; The 1999 Constitution of the Federal Republic of Nigeria and the 2003 Review of Local Government Councils in Nigeria. What this paper sets out to examine is the changing nature of Local government system in Nigeria right from the days of Native Authority s system to the present democratic one and their impacts on women and the poor. Historical Epochs of Local Government Administration in Nigeria Women and the Poor Strictly as per the compliance and regulations of: GJHSS-A Classification: FOR Code: 330104, 160509
Keywords: Handbook; Federal Republic; Native Authority